Sistem Keamanan Rumah Berbasis Internet of Things Menggunakan Metode Rapid Application Development - Nida, Milhatun; Nurazizah, Riri; Basyari, M. Farhan; Gunawan, Valmadia Alviana (Fakultas Teknik Universitas Hamzanwadi, 2024)
Conventional home security systems often lack the ability to monitor and respond in real-time, which makes them vulnerable to security breaches and delayed interventions. This research is an Internet of Things (IoT) based home security system that uses hard programming methods. This system consists of hardware that uses Arduino Uno, ESP32CAM and PIR sensor modules to detect movement, an ESP32CAM camera that takes pictures, and an Arduino Uno board that processes and transmits data. ESP32CAM takes images from the PIR sensor and sends them to the cloud server when it detects motion. The smartphone application then allows users to find out about potential disruptions in real-time through photo notifications. The system's ability to provide immediate visual evidence of suspicious activity, allowing for a rapid and informed response, determines the system's effectiveness. This system is also cheap and easy to use, so a wide range of users can use it. The use of easily accessible components and open-source software reduces costs and simplifies setup, enabling widespread adoption of this updated security product